Pyrimidine derivative as anti-liver cancer agent against EGFR Kinase Mutant T790M/L858R: a comprehensive in-silico approach - Roney, Miah; Issahaku, Abdul Rashid; Uddin, Md. Nazim; Akter, Mahmuda; Wilhelm, Anke; Mohd Fadhlizil Fasihi, Mohd Aluwi (Springer, 2026)
Liver cancer (LC) is the fourth most prevalent cause of cancer-related death worldwide. However, existing treatment options have limitations, as they do not consistently provide benefits to all patients. With an emphasis on pyrimidine derivatives, this study uses virtual screening approaches to find possible therapeutic agents against LC. These techniques include ADMET prediction, molecular docking, molecular dynamics (MD) simulations, density functional theory (DFT), and network pharmacology analysis. Fifteen compounds (1, 4, 6, 9, 16, 18, 27, 33, 38, 39, 40, 43, 44, 49, and 50) were selected for molecular docking studies against the EGFR kinase mutant T790M/L858R (PDB ID: 3W2Q) based on their favorable drug-like properties as determined by ADMET analysis. Compound 9 had the best Prime MM/GBSA score of -51.55 kcal/mol and the strongest binding affinity of -7.9 kcal/mol among the compounds that were chosen. It formed several hydrogen bonds with significant residues, including Lys745, Thr854, Met793, and Gln791, in the active site of the EGFR kinase mutant T790M/L858R. These interactions were superior to those of the reference compound (Erlotinib), which had a binding affinity of -6.4 kcal/mol and an MM/GBSA score of -52.51 kcal/mol. The enhanced stability of compound-9 over Erlotinib and the apo protein was also confirmed by molecular dynamics (MD) simulations, as evidenced by significant parameters such as RMSD, RMSF, radius of gyration (RoG), hydrogen bond interactions, principal component analysis (PCA), dynamic cross-correlation matrix (DCCM), and free energy landscape (FEL) analysis. Furthermore, the binding free energy of compound-9 was − 39.62 kcal/mol, while that of Erlotinib was − 42.13 kcal/mol. Network pharmacology research identified EGFR as a key target in the development of liver cancer (LC), since Gene Ontology (GO) and KEGG enrichment studies indicate that compound-9 may exert its inhibitory effects through several pathways, including the EGFR kinase pathway. These findings highlight the potential of compound-9 as a drug to treat LC.